Feasibility of harnessing nuclear energy in Singapore. - Yeo, Ronald Wei Shen. (2011)
Nuclear energy has been harnessed around the world. Its increased usage has outlined its importance as an alternative source of energy to the deteriorating fossil fuels. The rising prices of fossil fuels have hastened our search for alternative sources of energy and the increasing demand for electricity has motivated us to explore nuclear energy, which offers a low production cost for electricity when compared to other sources.